Du vrai, du beau et du bien - Cousin, Victor 1792-1867 (Brussels Typographie et librairie de C.-J. Fonteyn, 1854)
The publication of Du vérité, du beau, du bien, in 1853, by Victor Cousin, then aged sixty-one, marked the long-awaited return to favor of the old philosopher in liberal Catholic circles. Essentially, however, this book is nothing other than the resumption of a work published for the first time in 1818 and a second time in 1846. But from one to the other of these editions, Cousin corrects and attenuates a statement which had previously shocked and had contributed to giving credence to the idea that his philosophy was purely and simply demarcated from that of Hegel.
Victor Cousin was a French Kantian philosopher. He was the founder of "eclecticism", a briefly influential school of French philosophy that combined elements of German idealism and Scottish Common Sense Realism. As the administrator of public instruction for over a decade, Cousin also had an important influence on French educational policy. His philosophical lectures on the True, the Beautiful, and the Good derive from philosophy courses taught at the Faculté des lettres in Paris in the year 1818.
Originally published in 1844
Ex libris J. Pion 1883 (manuscript)
Augmentée d'un appendice sur l'art Français
Keywords: 19th Century (1801-1900); Esthetics; Romanticism; France